Guide to Targeted Therapies: EGFR mutations in NSCLC - Cappuzzo, Federico (Springer International Publishing : Imprint: Adis, 2014)
Guide to Targeted Therapies: EGFR Mutations in NSCLC is a speedy and up-to-date review, which discusses EGFR mutations, testing methods and technology, current and emerging therapies, and resources that clinicians can provide to their patients. Busy healthcare professionals who want a quick review of EGFR gene mutations as well as a summary of current therapies will benefit from this succinct guide.